Changes of in vitro potency of anticoagulant drugs are similar between patients with cirrhosis due to alcohol or non-alcoholic fatty liver disease. Issue 150 (February 2017) - Bos, Sarah; Potze, Wilma; Siddiqui, Mohammad S.; Boyett, Sherry L.; Adelmeijer, Jelle; Daita, Kalyani; Lisman, Ton; Sanyal, Arun J.
Highlights: In vitro potency of common anticoagulants differs substantially between patients with cirrhosis and controls. The hemostatic changes in patients with cirrhosis of different etiologies are similar but not identical. No differences were found in potency of LMWH, apixaban, and dabigatran between alcohol- or fatty liver-induced cirrhosis.